HAK SIPIL AGAMA (HSA) DALAM PIAGAM MADINAH - Ichrom, Muhamad (Institut PTIQ Jakarta, 2020)
In this article discusses the Civil Rights of Religion (HSA). This right includes freedom to establish religion and beliefs of one's own choice, and freedom, both individually and jointly with others, both public and private, to practice their religion and beliefs in worship, observance, practice, and teaching